2006
DOI: 10.1371/journal.pbio.0040020
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Membrane Topology and Heteromeric Function of Drosophila Odorant Receptors In Vivo

Abstract: Drosophila olfactory sensory neurons (OSNs) each express two odorant receptors (ORs): a divergent member of the OR family and the highly conserved, broadly expressed receptor OR83b. OR83b is essential for olfaction in vivo and enhances OR function in vitro, but the molecular mechanism by which it acts is unknown. Here we demonstrate that OR83b heterodimerizes with conventional ORs early in the endomembrane system in OSNs, couples these complexes to the conserved ciliary trafficking pathway, and is essential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
901
3
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 874 publications
(970 citation statements)
references
References 88 publications
37
901
3
2
Order By: Relevance
“…The domain that is most conserved among all Gr genes is located in the region encoding the putative seventh transmembrane domain at the carboxy terminus, a domain that is also shared with the Or genes (this domain was used as a signature motif in one study that lead to the discovery of the fly taste receptors [36]). Interestingly, Drosophila odorant receptors (ORs) were recently shown to have an inverse membrane topology compared to typical GPCRs, with an intracellular amino terminus and an extracellular carboxy terminus, and it has been suggested that they may use an alternative, non-G protein-based signaling pathway [44]. Whether GRs adopt a similar membrane topology and, if so, how this topology might affect downstream signaling remain to be determined.…”
Section: Gustatory Receptor Familymentioning
confidence: 99%
“…The domain that is most conserved among all Gr genes is located in the region encoding the putative seventh transmembrane domain at the carboxy terminus, a domain that is also shared with the Or genes (this domain was used as a signature motif in one study that lead to the discovery of the fly taste receptors [36]). Interestingly, Drosophila odorant receptors (ORs) were recently shown to have an inverse membrane topology compared to typical GPCRs, with an intracellular amino terminus and an extracellular carboxy terminus, and it has been suggested that they may use an alternative, non-G protein-based signaling pathway [44]. Whether GRs adopt a similar membrane topology and, if so, how this topology might affect downstream signaling remain to be determined.…”
Section: Gustatory Receptor Familymentioning
confidence: 99%
“…Measuring neuronal activity in these cells is an important step toward understanding the basic coding principles, as well as the spatial and temporal dynamics, of sensory systems. The fruit fly Drosophila melanogaster is widely used as a genetic model organism to uncover basic mechanisms of taste coding and odor perception [1][2][3][4][5][6][7] . Recent insights into the molecular and functional mechanisms of sensory perception in Drosophila have been achieved by the use of single-sensillum recordings of adult taste or olfactory sensilla 1,4,[8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Note: This table is not an exhaustive list of all centrosome and cilia components mapped. Due to space constrain, only references for mutants and/or markers for each gene are mentioned in the list [15,16,19,21,31,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Also, for more information about the genes visit www.flybase.org.…”
Section: Visualizing Directly or Immunostaining Of Centrosomes And CImentioning
confidence: 99%